2014
DOI: 10.1186/s40364-014-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

A panel of DNA methylation markers reveals extensive methylation in histologically benign prostate biopsy cores from cancer patients

Abstract: BackgroundMen with a negative first prostate biopsy will undergo one or more additional biopsies if they remain at high suspicion of prostate cancer. To date, there are no diagnostic tests capable of identifying patients at risk for a positive diagnosis with the predictive power needed to eliminate unnecessary repeat biopsies. Efforts to develop clinical tests using the epigenetic signature of cores recovered from first biopsies have been limited to a few markers and lack the sensitivity and specificity needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Thus, it would be of potential future clinical relevance to investigate the possible existence of PC-associated TFF3 hypomethylation field effects in morphologically non-malignant prostate needle biopsies, which in turn might be used to predict the need for repeat biopsy. The existence of epigenetic cancer field effects in relation to PC has previously been reported for a number of aberrantly hypermethylated genes [ 48 , 49 , 50 , 51 ], but further studies are needed to investigate if this is also the case for TFF3 promoter hypomethylation. Moreover, non/minimally-invasive biomarkers that can accurately predict the need for initial/repeat prostate biopsy are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be of potential future clinical relevance to investigate the possible existence of PC-associated TFF3 hypomethylation field effects in morphologically non-malignant prostate needle biopsies, which in turn might be used to predict the need for repeat biopsy. The existence of epigenetic cancer field effects in relation to PC has previously been reported for a number of aberrantly hypermethylated genes [ 48 , 49 , 50 , 51 ], but further studies are needed to investigate if this is also the case for TFF3 promoter hypomethylation. Moreover, non/minimally-invasive biomarkers that can accurately predict the need for initial/repeat prostate biopsy are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Due to field‐effects, cancer‐specific hypermethylation of certain gene promoters (e.g. GSTP1 ) has been shown to be detectable in morphologically benign prostate tissues adjacent to cancer, and to thus potentially indicate the need for repeat biopsy (Brikun et al., 2014; Trock et al., 2012; Troyer et al., 2009). Of note, in a separate study, we have recently observed that SLC18A2 DNA methylation can be detected in a subset of cancer‐negative diagnostic biopsies from patients with prostate cancer (Møller et al., unpublished data, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Many large-scale studies have reported an association between PC and methylation alterations in the GRASP gene coding for a general receptor for phosphoinositide-1-associated scaffold protein [ 60 ]. Further research concerning histologically benign prostate biopsy cores from cancer patients suggests that this marker is more likely to be methylated in histologically detectable cancer and may represent later events [ 61 ].…”
Section: Resultsmentioning
confidence: 99%